Research Credibility Analysis And Quality Test Of Supervisors At The Ministry Of Religion, Pangkalpinang City - Kartika Sari; Siti Patimah; Agus Pahrudin; Agus Jatmiko; Koderi (International Journal of Educational Research & Social Sciences, 2021)
Professional supervisors are supervisors who have competencies including research and development competencies. Research and development competence has eight competency indicators. The challenge in the world of education is the quality and equity of education. One of the components that determine quality is a supervisor who has high professionalism. Two of them relate to the supervisor's ability to master educational research and development concepts and the other six relate to the supervisor's ability to conduct research and educational guidance to teachers. The focus and purpose of this study is to describe and analyze the Competence of Supervisors at the Ministry of Religion of Pangkalpinang City. This research is a qualitative descriptive study. Data collection is done by observation, questionnaires (questionnaires), interviews, and documentation. The results of this study indicate that: (1) The ability of supervisors in the field of research and development aspects of mastery of the concept of approaches, types and research methods is "quite high".The ability of supervisors in the field of research and development aspects of mastery of concepts in determining supervisory issues that are important to be researched is "high". (3) The ability of supervisors in the field of research and development aspects of the preparation of educational research proposals, both qualitative research and quantitative research is "very low". (4) The ability of supervisors in the field of research and development aspects of carrying out educational research, and formulating educational policies that are beneficial to the main tasks and responsibilities of supervisors is "very low". (5) The ability of supervisors in the field of research and development aspects in managing and analyzing data on educational research results, both qualitative research and quantitative research, is “